L'Apertura Della Missione In Cina: Un centenario per "fare memoria" del cammino missionario dell'Ordine (1925-2025) - Fiasconaro, Paolo (Miscellanea francescana, 2025)
The centenary of the mission in China, founded by the Friars Minor Conventual, provided the occasion for the publication of the book, Cina - L'alba missionaria [China - The Missionary Dawn]. This article, a summary of part of the book, off ers the most relevant and signifi cant information related to the missionary events of the Church and the Order in the early decades of the 20th century. The sad story of various suppressions and military confl icts halted the missionaries' activity, but after the restoration of religious life and papal teaching related to the missions, the Conventual family renewed its charismatic character. The focus of the work is obviously on the beginnings and development of the mission in China and on the fi rst four Apostolic Prefects, all Conventual friars. Furthermore, information is provided regarding other Conventual missionary realities of the time - Japan and Zambia - as well as brief news on the foundations established after the Second World War up to the present day.